Effect of laser photobiomodulation combined with hydroxyapatite nanoparticles on the osteogenic differentiation of mesenchymal stem cells using artificial intelligence: An in vitro study - de Melo, Eloiza Leonardo; Miranda, Jéssica Meirinhos; de Souza Rolim Lima, Vanessa Bastos; Gaião, Wyndly Daniel Cardoso; de Vilhena Amorim Tostes, Braulio; Rodrigues, Claudio Gabriel; da Silva, Márcia Bezerra; Júnior, Severino Alves; Perger, Edson Luiz Pontes [UNESP]; Bispo, Mávio Eduardo Azevedo; de Martínez Gerbi, Marleny Elizabeth Márquez (Public Library of Science (PLoS), 2024)
Aim To evaluate in vitro the effect of laser photobiomodulation (PBM) combined or not with 30-nm hydroxyapatite nanoparticles (HANp), on the osteogenic differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs) by morphometric analysis using artificial intelligence programs (TensorFlow and ArcGIS). Methods UC-MSCs were isolated and cultured until 80% confluence was reached. The cells were then plated according to the following experimental groups: G1 –control (DMEM), G2 – BMP-2, G3 –BMP-7, G4 –PBM (660 nm, 10 mW, 2.5 J/cm2, spot size of 0.08 cm2), G5 – HANp, G6 –HANp + PBM, G7 –BMP-2 + PBM, and G8 –BMP-7 + PBM. The MTT assay was used to analyze cell viability at 24, 48 and 72 h. Osteogenic differentiation was assessed by Alizarin Red staining after 7, 14 and 21 days. For morphometric analysis, areas of osteogenic differentiation (pixel2) were delimited by machine learning using the TensorFlow and ArcGIS 10.8 programs. Results The results of the MTT assay showed high rates of cell viability and proliferation in all groups when compared to control. Morphometric analysis revealed a greater area of osteogenic differentiation in G5 (HANp = 142709,33±36573,39) and G6 (HANp + PBM = 125452,00 ±24226,95) at all time points evaluated. Conclusion It is suggested that HANp, whether combined with PBM or not, may be a promising alternative to enhance the cellular viability and osteogenic differentiation of hUC-MSCs.